Implementation of the PUSPAH Program by PT Gane Permai Sentosa in South Halmahera: Social Mapping and Community Development Strategies - Muslimah; M. Yuda Pranata; Fikri Imam Riadhi (Prospect: Jurnal Pemberdayaan Masyarakat, 2025)
The implementation of the Pusat Pengolahan Sampah (PUSPAH) program conducted by PT Gane Permai Sentosa (GPS) in South Halmahera, North Maluku, with a particular focus on the role of social mapping as a foundation for effective community development. The social mapping carried out in Kawasi Village provided a comprehensive understanding of the community’s social, economic, and institutional conditions, including their needs, potentials, and challenges. The information obtained served as the basis for designing targeted interventions, such as strengthening village institutions, enhancing human resource capacities through training and education, and promoting diversified local economic activities to support sustainable development. The implementation of PUSPAH in Kawasi Village demonstrates how data-driven programs can effectively address environmental problems while generating economic value through an Integrated Waste Management (IWM) approach. Impact evaluation revealed significant improvements across environmental, social, and economic dimensions, although sustainability challenges persist due to limited technical capacity, infrastructure, and local resources. The study underscores that integrating social mapping with program implementation can substantially contribute to achieving local sustainable development goals and reinforce the company’s social license to operate.